PENGARUH KEBIJAKAN DIVIDEN, EARNING VOLATILITY, DAN LEVERAGE TERHADAP VOLATILITAS HARGA SAHAM PADA PERUSAHAAN NON-FINANCING YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2010-2014 - Jannah, Raudhatul; Haridhi, Musfiari (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2016)
The research examines the effect of dividend policy, earnings volatility, and leverage on share price volatility of non financing companies listed in Indonesia Stock Exchange in 2010-2014. Dividend policy variabel using dividend payout ratio and leverage variabel using debt to equity ratio. Secondary data were sourced from the financial statements, published by the capital market reference center at the Indonesia Stock Exchange. The research type used in this research is hypothesis testing, by using simple random sampling method. There are 195 samples of the data that become the object to be researched. This research uses multiple linear regression analysis to test the hypothesis. The results of this research show that simultaneous of dividend payout ratio, earnings volatility, and leverage have effect on share price volatility. Partially the research shows that (1) dividend payout ratio have negative effect on share price volatilty, (2) earnings volatility have positive effect on share price volatility, and (3) leverage have positive effect on share price volatility.Keywords: Dividend Policy, Earnings Volatility, Leverage, and Share Price Volatility